`int e^(sqrt(2x)) dx` Find the indefinite integral by using substitution followed by integration by parts.

Expert Answers

An illustration of the letter 'A' in a speech bubbles

To evaluate the given integral problem` int e^(sqrt(2x))dx ` us u-substituion, we may let:

`u = 2x` then `du = 2 dx` or `(du)/2 = dx` .

Plug-in the values `u = 2x ` and `dx = (du)/2` , we get:

`int e^(sqrt(2x))dx =int e^(sqrt(u))* (du)/2`

Apply the basic integration property: `int c*f(x) dx = c int f(x) dx` .

`int e^(sqrt(u))* (du)/2=1/2 int e^(sqrt(u)) du`

Apply another set of substitution, we let:

`w = sqrt(u)`

Square both sides of `w =sqrt(u)`, we get: `w^2 =u`

Take the derivative on each side, it becomes: `2w dw = du` 

Plug-in `w =sqrt(u)` and `du = 2w dw` , we get: 

`1/2 int e^(sqrt(u)) du =1/2 int e^(w) * 2w dw`

                                     ` = 1/2 * 2 inte^(w) *w dw`

                                     `= int e^w * w dw` .

To evaluate the integral further, we apply integration by parts:`int f* g' = f*g - int g *f'

Let: `f =w` then `f' = dw`

       `g' = e^w dw` then `g = e^w`

Applying the formula for integration by parts, we get:

`int e^w * w dw = w*e^w - int e^w dw`

                       `= we^w -e^w +C`

Recall we let: `w =sqrt(u)` and `u = 2x ` then `w =sqrt(2x)` .

 Plug-in `w=sqrt(2x)` on  `we^w -e^w +C` , we get the complete indefinite integral as:

`int e^(sqrt(2x))dx =sqrt(2x) e^(sqrt(2x)) -e^(sqrt(2x)) +C`

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial